From Frozen Conflict to Mobile Boundary: Youth Perceptions of Territoriality in War-Time Ukraine. Issue 1 (February 2018) - Fournier, Anna
Scholarly and media sources have often described the conflict in Ukraine's east as a potential "frozen conflict" similar to other such conflicts in the post-Soviet space. My interviews with young Ukrainian citizens reveal that many imagine not a stalemate but rather a continuous repositioning of the border between Ukraine and Russia. I use the term "mobile boundary" to describe the widespread belief within my sample that the Ukraine-Russia boundary may move back and forth within Ukrainian territory. Some interviewees express their willingness, at least in theory, to surrender the contested territories of Donetsk and Luhansk, but it is their fear of Russian encroachment beyond those territories that provides the rationalization for continued military defense of the Donbas.